Sprach-Spiel-Kunst Ein Dialog zwischen Wissenschaft und Praxis - Winter-Froemel, Esme (The Dynamics of Wordplay, 2019)
What does wordplay teach us about the function of language and communication? What creative open spaces are used in wordplay, and what are the rules and limits that govern the game? The volume presents ideas of masters of wordplay from literature, film, cabaret, and poetry slams along with brief scientific analyses. The dialogue between theory and practice reveals the diverse complexity of language play.